Pendampingan Pelayanan Usaha Mikro Kecil Menengah (UMKM) dalam Pengurusan Legalitas & Branding Usaha di Kelurahan Karanganyar - Ilmiyatur Rosidah; Galang Febriansyah; Sendik Saputra; Atika Dwi Rahmania; Muhammad Rosul; Wasilatul Choiriyah (Lembaga Pengembangan Kinerja Dosen, 2024)
Micro, Small and Medium Enterprises (MSMEs) are business activities that are very helpful in improving the community's economy. In carrying out MSMEs activities, it is important for business actors to carry out legality and product branding in the business they are running. In Karanganyar village, there are several MSMEs that have not yet carried out legality and product branding, so the solution provided is to provide counseling and assistance to carry out legality and product branding. The purpose of legality and product branding in MSMEs is to provide a strong foundation for the sustainability of a legally protected business, increase trust and competitiveness in entrepreneurship, market access will be wider, and increase added value and loyalty. The result of the assistance activities in managing the legality and branding of MSMEs products in Karanganyar village is that MSMEs get a Business Identification Number (BIN), and receive assistance in making product photos and designing banners.